Fine-Tuning Surface Properties of Perovskites via Nanocompositing with Inert Oxide toward Developing Superior Catalysts for Advanced Oxidation - Li, J.; Miao, J.; Duan, Xiaoguang; Dai, J.; Liu, Q.; Wang, Shaobin; Zhou, W.; Shao, Zongping (Wiley, 2018)
© 2018 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim Cost-effective, stable, and highly efficient heterogeneous catalyst is the key challenge for wastewater treatment based on Fenton-like advanced oxidation processes. Perovskite oxides offer new opportunities because of their versatile compositions and flexible physiochemical properties. Herein, a new strategy is proposed that is different from the frequently used alien-metal doping, to tune surface properties of perovskite oxides by nanocompositing perovskite with inert oxide, resulting in improved activity and stability for catalytic oxidation. By in situ modification of LaFeO3 with inert La2O3 oxide through one-pot synthesis, several important surface properties such as surface defects, H2O2 adsorption capacity, Fe2+ concentration, and charge-transfer rate were improved, as well as resistance against iron leaching. In performance evaluation, among the various materials, La1.15FeO3 (L1.15FO) composite shows the highest Fenton activity (0.0402 min-1) for activating H2O2 to oxidize methyl orange, 2.5 times that of the pristine LaFeO3. Notably, in situ electron paramagnetic resonance analysis and radical scavenging tests unveil a faster generation of singlet oxygen as the dominant reactive species over L1.15FO, consequently a novel non-radical activation mechanism is proposed. Such improved performance is assigned to the strong coupling effect between the nanosized LaFeO3 and La2O3 in the hybrids, which fine-tune the surface properties of LaFeO3 perovskite as superior Fenton catalysts.